The Research Workshop - Nvivo on IPMI Institute - Anantadjaya, Samuel PD; Lahuddin, Abdul Haris; Nawangwulan, Irma M; Pratama, Sasotya; Yulita F Susanti; Amelia Naim Indrajaya; Zahirsjah, Cut Sjahrifa; Hariandja, Hari Ara; Samuel, DC Ethan; Samuel, Daniella CE; Oktavianis, Yusrika; McNerney, Brian (CV. Media Digital Publikasi Indonesia, 2025)
The workshop featured in The Research Workshop (Volume 12) at the IPMI Institute in June 11, 2025 is concerned with the application of NVivo for advanced qualitative data analysis in research. Participants are introduced to NVivo's main functions such as importation, organization, and coding of many forms of data including text documents, surveys, and audio and video material. The hands-on sessions of the workshop are focused on real applications such as coding scheme development, integration of categorical data, and advanced querying techniques for identifying and interpreting patterns. Modeled for researchers and faculty alike, the intention of the program is to create new ways to achieve efficient and rigorous analyses in qualitative research, geared toward the application of these methods in real-world situations across disciplines. The session will also provide an introduction to some of those new NVivo features that are AI-assisted and will discuss the opportunities to enhance the analysis process as well as some limitations.